Through the mists of time: Sushrutha, an enigma revisited - Puthumana, Philip Philip (Medknow Publications, 2009)
Sushrutha had been viewed in textbooks of plastic surgery as belonging to the caste of potters who performed surgery in India. We have examined the available source documents and other references to the technology of the period to examine this assertion and are convinced that there is no evidence to support this. The period, technology and geographic references in Sushrutha Samhitha are correlated with settled positions on these to arrive at an understanding of the time and knowledge which is described. Source of erroneous interpretation of Sushrutha as a potter is also examined and clarified.